Explore Westonci.ca, the premier Q&A site that helps you find precise answers to your questions, no matter the topic. Experience the ease of finding reliable answers to your questions from a vast community of knowledgeable experts. Connect with a community of professionals ready to provide precise solutions to your questions quickly and accurately.
Sagot :
Answer:
(2, 5 )
Step-by-step explanation:
Given the 2 equations
2x + 3y = 19 → (1)
6x + 2y = 22 → (2)
Multiplying (1) by - 3 and adding to (2) will eliminate the x- term
- 6x - 9y = - 57 → (3)
Add (2) and (3) term by term to eliminate x
0 - 7y = - 35
- 7y = - 35 ( divide both sides by - 7 )
y = 5
Substitute y = 5 into either of the 2 equations and solve for x
Substituting into (1)
2x + 3(5) = 19
2x + 15 = 19 ( subtract 15 from both sides )
2x = 4 ( divide both sides by 2 )
x = 2
solution is (2, 5 )
Thanks for using our service. We aim to provide the most accurate answers for all your queries. Visit us again for more insights. We hope you found this helpful. Feel free to come back anytime for more accurate answers and updated information. Get the answers you need at Westonci.ca. Stay informed by returning for our latest expert advice.